Development of a Web-based Physical Education Digital Library - Redho, Muhammad; Hartati, Hartati; Aryanti, Silvi (Journal of Physical Education Health and Sport, 2023)
The research titled The Development of Digital-based Library in Improving Educative Knowledge of Students Majoring in Physical Education Study Program at Universitas Sriwijaya aimed to 1) establish a web-based digital library for first-semester Physical Education students at Universitas Sriwijaya and 2) determine the validity, practicality, and effectiveness of web-based digital library for first-semester Physical Education students at Universitas Sriwijaya. The method used in this research was RD, which described a product in the form of a web-based digital library for first-semester Physical Education students at Universitas Sriwijaya. The research results were material validation, resulting in a validity of 90%, language validation of 75% and media validation of 95%. The main trial resulted in a practicality of 91.63%, and in the operational trial, the practicality resulted in 86.8%, and the effectiveness of the media was included in the “effective” category with a percentage of 83.5%. From the research results, it can be concluded that developing a web-based digital library was valid, practical, and effective. It also can be used as a digital library for first-semester Physical Education students at Universitas Sriwijaya.